The potential of cenospheres production from Malaysian coal power plants - Salmia, Beddu; Mahyun, Zainoodin; Amalina, Basri; Zarina, Itam; Raudhah, Ahmadi; Teh Sabariah, Abd Manan (IOP Publishing Ltd, 2020)
Coal Combustion Waste (CCW) fly ash, main component of coal ash waste generated at the Coal-Fired Power Plant throughout the year that causes the presents of toxic metals in the ash. Hence, pose significant health threats towards humans and environment. Cenosphere is a coal combustion by-product obtained from fly ash in boilers of coal fired power plants. The properties of cenosphere including spherical, lightweight, good thermal stability, chemical proof, heat resistance making it to have improved insulation. The aim of this research was to investigate the potential of cenospheres production from three different coal fired power plants in Malaysia namely Jimah, Kapar and Manjung. The wet method was used for cenospheres separation from the fly ash. The percentages of cenospheres ranged from 1 to 1.2% of every 1000 gram of fly ash. The mean sizes were 95.86µm, 88.64µm, 49.04µm for Jimah, Kapar and Manjung respectively. Cenosphere evacuated by utilizing water as a medium, it will expend a lot of water and lead to water contamination cause of leaching of toxic material while extracting the cenosphere from fly ash. Nevertheless, any health and environmental impacts from the value-added physical application of cenospheres in civil engineering materials must be screened via strict monitoring and legislated guidelines.